A CHARACTERIZATION OF CAVAFY'S 18: CASCADING ENJAMBMENT AND THE SYLLABIC FORM. Issue 1 (3rd May 2020) - de Voogt, Alex
Abstract : The influence of Constantine Cavafy's (1863–1933) poetry outside of Greece has mainly proceeded through translations. Only in the last two decades has some attention been given to formal structures, such as meter and rhyme, which play a significant role in at least a third of his poems. Cavafy shows particular ingenuity creating one form, which is found in eighteen examples. It consists of visible hemistiches and a fixed syllabics structure. Cavafy built on the traditional structure of the Dekapentasyllavo or Greek folk song but allowed a flexible number of syllables, six or seven for either hemistich, together with a clear caesura. In later years, Cavafy would compromise the integrity of the meaningful phrase in each hemistich but never violated his own rules of syllabics. Syllabics look, feel, and sound different when they are applied in translation. They are a hidden structure with historical antecedents. Cavafy's 18 are not limited to a theme or subject, yet the lack of attention to the form of these poems obfuscates Cavafy's engagement with Modern Greek folk songs and his attempts to modernize their form.